PENGUATAN TATA KELOLA USAHA GULA AREN BERBASIS KOMUNITAS DIGITAL - Sandi Lubis; Kahar Kahar; Hardianti Hardianti; Muhammad Rais Rahmat Razak (Universitas Mataram, 2026)
This community service program was implemented to address the issues of low production efficiency, weak business governance, and limited market reach of Gula Aren products managed by CV. Insan Maiwa Mandiri in Kelurahan Bangkala, Kabupaten Enrekang. The program employed a community-based participatory approach integrating technology and local institutional strengthening, consisting of need assessments, integrated training, activation of the Digital Marketing and Production Management Platform (PDMP) based on Flutter (Android & Web), mentoring, and evaluations. from about 150 packages @100 grams to about 250 packages @100 grams per day), digitalized business records (≥85% of transactions recorded), and expanded market access through social media, a website, and national marketplaces. These findings indicate that applying digital technology through a smart community approach is effective in enhancing the performance and competitiveness of small community-based enterprises in rural areas.